Lipopolysaccharide-Binding Protein Downregulates Fractalkine through Activation of p38 MAPK and NF-κB - Xia Huang; Yi Zeng; Yujie Jiang; Yueqiu Qin; Weigui Luo; Shulin Xiang; Suren R. Sooranna; Liao Pinhu (Hindawi Limited, 2017)
Background. LBP and fractalkine are known to be involved in the pathogenesis of ARDS. This study investigated the relationship between LBP and fractalkine in LPS-induced A549 cells and rat lung tissue in an ARDS rat model. Methods. A549 cells were transfected with LBP or LBP shRNA plasmid DNA or pretreated with SB203580 or SC-514 following LPS treatment. An ARDS rat model was established using LPS with or without LBPK95A, SB203580, or SC-514 treatment. RT-PCR, western blotting, ELISA, immunofluorescence, coimmunoprecipitation, and immunohistochemical staining were used to study the expression of fractalkine and LBP and p38 MAPK and p65 NF-κB activities. Results. LPS increased LBP and reduced fractalkine. LBP overexpression further decreased LPS-induced downregulation of fractalkine and p38 MAPK and p65 NF-κB activation; LBP gene silencing, SB203580, and SC-514 suppressed LPS-induced downregulation of fractalkine and p38 MAPK and p65 NF-κB activation in A549 cells. LBP and fractalkine in lung tissue were increased and decreased, respectively, following LPS injection. LBPK95A, SB203580, and SC-514 ameliorated LPS-induced rat lung injury and suppressed LPS-induced downregulation of fractalkine by decreasing phospho-p38 MAPK and p65 NF-κB. Conclusions. The results indicate that LBP downregulates fractalkine expression in LPS-induced A549 cells and in an ARDS rat model through activation of p38 MAPK and NF-κB.